2 Chronicles : a commentary - Klein, Ralph W. (Hermeneia--a critical and historical commentary on the Bible., 2012)
This volume complete Ralph W. Klein's magisterial commentary on 1 and 2 Chronicles. Klein incorporates the breakthroughs of the last half-century of research and shows that the Chronicler used a text of Kings significantly different from the Masoteric text. --